First evidence for glial pathology in late life minor depression: S100B is increased in males with minor depression - Polyakova, Maryna; Sander, Christian; Arelin, Katrin; Lampe, Leonie; Luck, Tobias; Luppa, Melanie; Kratzsch, Jürgen; Hoffmann, Karl-Titus; Riedel-Heller, Steffi; Villringer, Arno; Schoenknecht, Peter; Schroeter, Matthias L. (Frontiers in Cellular Neuroscience, 2015)
Minor depression is diagnosed when a patient suffers from two to four depressive symptoms for at least two weeks. Though minor depression is a widespread phenomenon, its pathophysiology has hardly been studied. To get a first insight into the pathophysiological mechanisms underlying this disorder we assessed serum levels of biomarkers for plasticity, glial and neuronal function: brain-derived neurotrophic factor (BDNF), S100B and neuron specific enolase (NSE). 27 subjects with minor depressive episode and 82 healthy subjects over 60 years of age were selected from the database of the Leipzig population-based study of civilization diseases (LIFE). Serum levels of BDNF, S100B and NSE were compared between groups, and correlated with age, body-mass index, and degree of white matter hyperintensities (score on Fazekas scale). S100B was significantly increased in males with minor depression in comparison to healthy males, whereas other biomarkers did not differ between groups (p=0.10-0.66). NSE correlated with Fazekas score in patients with minor depression (r=0.436, p=0.048) and in the whole sample (r=0.252, p=0.019). S100B correlated with body mass index (r=0.246, p=0.031) and with age in healthy subjects (r=0.345, p=0.002). Increased S100B in males with minor depression, without alterations in BDNF and NSE, supports the glial hypothesis of depression. Correlation between white matter hyperintensities and NSE underscores the vascular hypothesis of late life depression.